On the phonetics of glottal stops and larangized phonation: Cases of Amerindian languages - Elías-Ulloa, José (2011)
In this study, I examine sorne of the articulatory and acoustic properties present in the phonetic realization of glottal stops. In particular, I focus on two tendencies languages show when they realize this type of segments: full closure of the vocal folds and creaky voice. I show through examining the language Boruca that creaky voice can occur without the aperiodic vibration ofthe vocal folds. In this language, a decrease of the fundamental frequency and intensity can serve alone as a phonetic cue to detect creaky voice. I also examine the influence that prosodic structure can have on restricting the spreading of creaky voice within a vowel. Particularly, 1 present the cases of two Panoan languages, Capanahua and Shipibo, in which vowels of syllables in strong prosodic positions tend to resist having creaky voice throughout their duration. In contrast, vowels that belong to weak syllables do tend to appear completely in creaky voice.